2016
DOI: 10.1136/bmjopen-2016-012726
|View full text |Cite
|
Sign up to set email alerts
|

Supervisors' perspective on medical thesis projects and dropout rates: survey among thesis supervisors at a large German university hospital

Abstract: ObjectivesTo identify underlying causes for failure of medical thesis projects and the constantly high drop-out rate in Germany from the supervisors' perspective and to compare the results with the students' perspective.SettingCross-sectional survey. Online questionnaire for survey of medical thesis supervisors among the staff of Charité—Universitätsmedizin Berlin, Germany. Published, earlier longitudinal survey among students for comparison.Participants1069 thesis supervisors participated.Data extraction and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 40 publications
1
21
0
Order By: Relevance
“…Further research is needed to determine the amount of terminated projects and the reasons for this. This is seemingly being viewed rather diversely by students and supervisors [27]. …”
Section: Discussionmentioning
confidence: 99%
“…Further research is needed to determine the amount of terminated projects and the reasons for this. This is seemingly being viewed rather diversely by students and supervisors [27]. …”
Section: Discussionmentioning
confidence: 99%
“…However, the review of the literature leads to the conclusion that there are few studies explicitly focusing on master thesis projects. Studies on completion of thesis projects mostly concern the doctorate thesis [16,17] while studies on master thesis completion tend to focus on the whole program, not the thesis specifically [18][19][20]. Furthermore, most studies have used a qualitative approach to investigate factors for thesis completion; single factors have been looked at in an isolated way with a primary focus on student variables and on completion factors (and not on non-completion and supervisor variables) [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…It seems that one common deficiency in methodological training for medical students is statistics. Earlier studies on German medical doctor candidates showed that more than half of the students need more assistance with statistics 9. A measure of attitudes found that medical students were not very active in their study of statistics 10.…”
Section: Discussionmentioning
confidence: 99%